Kajian Yuridis Terhadap Perubahan Nama pada Seseorang di Kabupaten Badung - Putu Gede Surya Dharma Sadana; Ni Luh Made Mahendrawati; I Wayan Arthanaya (Jurnal Preferensi Hukum, 2022)
The number of changes in the name of a person in Badung Regency which has an impact on the preparation of an administrative system, deserves the attention of the government. This is the case in this study, namely the regulation of changing the name of a person in Badung Regency and the legal consequences of changing the name of a person in Badung Regency. The purposes of this study are to analyze the regulation of changing someone's name in Badung Regency and the legal consequences of changing someone's name in Badung Regency. The type of research used in this study is a normative legal research type with a statutory, conceptual and case approach. Data collection techniques are carried out through documentation studies and literature studies by collecting legal sources in the form of primary and secondary legal sources. After the data has been collected, it is then analyzed using interpretive interpretation techniques and presented in descriptive form. The results of the study revealed that the name change was carried out based on the determination of the district court where the applicant was. Next, the change of name must be registered by the person who changed his name to the civil registry that issued the civil registration deed at least 30 days after the resident received a copy of the district court decision. The next civil registry will make marginal notes on the register of civil registration deeds and quotations of civil registration deeds.